(untitled) (GEON Journal (Management, Organizations and Business), 2016)
This article presents the results of research conducted wage compensation system for micro and small businesses in the town of Restrepo-Meta; the findings will be useful for the business community because it strengthens their knowledge against compensation systems. For the development of this research an instrument containing questions regarding on hiring, salary, salary increases and incentives applied. As for the results in engagement it was determined that the most widely used type of contract is verbal and is used to link the workforce full-time staff; and most times the labor contract ends with the decision of some parties. With regard to wages it is mainly found that slightly more than half pays a SMMLV, this wage is fixed, bi-weekly and paid in cash, and its establishment is mostly personal opinion that is the owner. Faced with wage increases it found that slightly less than half make no wage increase and for those who perform the most influential factor when you determine it is the worker’s performance. And finally, on work incentives it could be concluded that these are provided mainly by accomplishing goals and holidays; and granted more often are time and money.